(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Celem pracy jest przedstawienie obecnego stanu prawnego w zakresie spraw nieletnich uregulowanego w ustawie o zapobieganiu i zwalczaniu demoralizacji i przestępczości nieletnich. Istniejący w Polsce ogólny system wychowania młodzieży nie jest jeszcze wystarczający i wymaga stałych ulepszeń, rozbudowy istniejących i funkcjonujących instytucji, wprowadzenia nowych metod i form działania. Przestępczość nieletnich jest przedmiotem badań od wielu lat. Liczne badania w tej materii są prowadzone w Zakładzie Kryminologii Instytutu Nauk Prawnych Polskiej Akademii Nauk oraz wielu ośrodkach uniwersyteckich. Badania kryminologiczne wskazują na złożoność tych problemów i pozwalają na wskazanie na istotne zagadnienia dla profilaktyki i zwalczania demoralizacji nieletnich. The aim of this paper is to present the current legal situation regarding juvenile cases as governed by the Act on the Prevention and Combating of Juvenile Demoralisation and Delinquency. The existing general system of youth education in Poland is not yet sufficient and requires constant improvements, expansion of existing and functioning institutions, as well as introduction of new methods and forms of action. Juvenile delinquency has been the subject of research for many years. Numerous studies on this matter are being carried out at the Department of Criminology of the Institute of Legal Sciences of the Polish Academy of Sciences and a number of university centres. Criminological research shows the complexity of these problems and makes it possible to identify important issues for the prevention and combating of juvenile demoralisation.